Where do the Limits of the Discretionary Power of the President of Romania in Regard to the Withdrawal of Decorations end? Array - Zorzoana, Alina (Acta Universitatis Danubius. Juridica, 2020)
In the context of debates that occurred in the public spaces in regard to the decision of the President of Romania to withdraw decorations awarded to public persons, this study intends to perform an analysis in regard to the limits of the discretionary power of the head of state in this case. Without involving the political component of this case, our research shall be limited to the applicable legal framework (insofar there is any), the attributions of the Chancellery of Orders, the conditions of awarding and withdrawing decorations, inclusively the necessity of motivating decrees as an essential condition for the validity of the administrative deed. The study concurrently also refers to a comparative analysis between similar situations of withdrawing decorations.